Substance removal with adsorption. Issue 5 (September 2018) - Unknown
Abstract : The manufacture of pharmaceuticals frequently results in effluent being released when the production plants are cleaned. However, they can be removed from the wastewater by adsorptive treatment processes. SARATECH ® adsorbents from Blücher are especially well suited for this task.